Volume growth responses of Scots pine and Norway spruce to nitrogen fertilization: quantitative synthesis of fertilization experiments in Finland - Johanna Jetsonen; Annamari Laurén; Heli Peltola; Katariina Laurén; Samuli Launiainen; Marjo Palviainen (Silva Fennica)
The effects of nitrogen (N) fertilization on tree growth have been studied widely in boreal forests in Finland, but a quantitative synthesis is still lacking. We performed a quantitative synthesis on volume growth responses to N fertilization in Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) Karst.) stands in experiments established on mineral soils across Finland. Our study employed findings of 9 published studies including 108 Scots pine and 57 Norway spruce observations covering a wide range of N fertilization treatments, as well as forest stand- and climatic conditions. Based on these observations, we built linear mixed models to describe the N fertilization-induced annual volume growth response of Scots pine and Norway spruce stands. Our models showed that the N dose was the best predictor for volume growth response, and the growth response increased linearly with increasing N dose for both tree species. The volume growth responses also increased along with an increase in mean annual precipitation. The annual volume growth response decreased with the time since fertilization. For Scots pine, the best model also contained site fertility; increase in site fertility increased the volume growth response. These findings emphasize the need for site-specific precision fertilization schemes to sustainably improve growth and carbon sequestration of boreal forests.